Development and Validation of an RP-HPLC Method for the Quantification of Isolongifolene in Chitosan-Based Nanoparticle Formulation - Yadav, Poonam; Parekh, Bhavin; Dasgupta, Ramesh Kumari; Brahma, Pratyush Kumar; Rathod, Mayuri A.; Prajapati, Paresh A.; Kesharwani, Sunayana; Chaudhari, Hardik C. (Journal of Neonatal Surgery, 2025)
This study presents the development and validation of a robust and precise reverse-phase high-performance liquid chromatography (RP-HPLC) method for the quantification of Isolongifolene in chitosan-based nanoparticle formulations. The method was optimized and thoroughly validated in accordance with ICH Q2(R1) guidelines, focusing on specificity, precision, accuracy, linearity, and robustness. Specificity tests demonstrated no interference from matrix components, ensuring reliable quantification of Isolongifolene. The precision was validated by analyzing six replicates of the same batch, yielding a %RSD of less than 2%. The method showed excellent linearity over a concentration range of 50% to 150% of the intended strength, with a correlation coefficient (R²) of 0.998. Accuracy was confirmed through recovery studies, with mean recovery rates between 98.5% and 101.7%. Robustness testing revealed that slight variations in chromatographic conditions, including column temperature, mobile phase composition, and detection wavelength, had minimal effect on the method's performance, further confirming its stability. The method's system suitability parameters, including retention time, asymmetry factor, and theoretical plates, adhered to regulatory criteria, making it suitable for routine analysis of Isolongifolene in pharmaceutical formulations.